MODERN ISSUES IN TRANSLATION AND INTERLINGUAL COMMUNICATION - Khamrayeva Nilufar Tuyg’un qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation: This article analyzes modern problems encountered in the process of translation and in the system of interlingual communication. In the context of globalization, the strengthening of cultural, political, and economic relations among different nations has further increased the demand for translation activities. At the same time, issues such as semantic ambiguity, cultural differences, the inability to fully convey the national context, and the limitations of automatic translation systems have become highly relevant. The article examines the translator’s linguistic and cultural competence, the principle of communicative equivalence, as well as the advantages and drawbacks of translation tools based on artificial intelligence. It also highlights the importance of accurately conveying cultural context in interlingual communication, the necessity of preserving connotative meanings, and the role of modern translation technologies. The results of the study show that for effective translation and successful interlingual communication, not only technical tools but also the harmony of human intellect, cultural knowledge, and communicative competence play a crucial role.